Structural and optical properties of graphene-based zinc selenide composites prepared via microwave-assisted hydrothermal method for photovoltaic and photonics application - Lee, Han Kee (2019)
The global energy demands will more than supply by the year 2040. In order to resolve this problem, the energy should be generated by using renewable source or reduce the energy consumption. Zinc selenide (ZnSe) has been widely used in applications such as LED, solar cell and other. There were researches on enhancing ZnSe properties by doping or mixing with other materials but there is not much reports on forming graphene-based ZnSe composite. In this research, graphene-based zinc selenide composites were synthesized via microwave-assisted hydrothermal method. Microwave-assised hydrothermal method was employed as it can greatly reduce the energy consumption, cost and time. Home made hydrothermal autoclave was used to charge the precursor and heated in the microwave oven. Through this method, the energy consumption, cost and reaction time were drastically reduced by 99%. The optimized condition to synthesis graphene-based ZnSe composite was using 0.100 mole of NaOH, 2ml of diethanolamine (surfactants) heated for 3 minutes under 700 W microwave irradiation power. The structural, morphological and optical properties of graphene-based zinc selenide composites were then characterized with X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Raman Spectroscopy, Field Emission Scanning Electron Microscope (FESEM), Atomic Force Microscope (AFM), Diffuse Reflectance Spectroscopy (DRS) and Photoluminescence (PL) Spectroscopy. For ZnSe/GO and ZnSe/GNP composites, cubic ZnSe was grown on the GO or GNP sheets which was observed in the AFM image. The spherical shape of pure ZnSe changed to nanoflakes as GO or GNP was added in as precursor. The purity of ZnSe formed was reduced from 100 % of ZnSe to 86.3 % as concentration of GO or GNP added was higher. The electron density in the sample was then determined via Fourier mapping. The electron density occupied the empty spaces within the cubic structure of ZnSe as GO or GNP was added. From Raman spectra, it can be confirmed that ZnSe/GO and ZnSe/GNP composites were formed. The intensity ratio between D band and G band (Id/Ig) was ~1 for ZnSe/GO composites and ~0.3 for ZnSe/GNP composites. The chemical bonding of GO and GNP was determined via FTIR technique where C=C, C-O, CH3, C-H and –COO- bonding were found in ZnSe/GO and ZnSe/GNP composite. The optical band gap of ZnSe is 2.64 eV. The band gap changed to 2.62 eV and 3.02 eV as GO and GNP were added, respectively. The sample was excited by a wavelength of 290 nm where the PL emission peak for all samples were centered at ~466 nm. The samples were tested on the photovoltaic and photonic applications. The solar efficiency was increased from 0.19% (pure ZnSe) to 1.61 % when GO was added and 11.88 % when GNP is added. In addition, it has been proved that graphene-based ZnSe composite managed to generate femtosecond pulse of ~540 fs which can become a promising materials in photonics application such as micro- or nano-machining technology, non-linear imaging and microscopy and micro- and nano-surgery technology. Modification of ZnSe to form ZnSe/GO and ZnSe/GNP composite will change the electron density, morphology and optical properties. This research provides a fundamental knowledge to support the properties required for photovoltaic and photonics application.